The Advantageous Application of Spirulina in Mitigating Lipid Profile and Glycemic Alterations induced by a High Calorie Diet in Wistar Rat - Kouidri, Amel; Meribai, Amel; Khattabi, Latifa; Defairi, Djamila; Flici, Samir; Akkal, Salah (Jordan Journal of Pharmaceutical Sciences, 2026)
An unbalanced diet inevitably leads to weight and metabolic dysfunction. Spirulina (Arthrospira platensis) can be a useful supplement to remedy this situation. This work aims to study the effect of spirulina at 2% in the diet of unbalanced Wistar rat on weight and some biochemical parameters related to metabolism. The Wistar rats were being altered by a prolonged introduction of a high calorie diet. They receive the following experimental diets: a standard diet (S), a high calorie diet (H) and a diet enriched with Spirulina (SP). Rats had ad libitum access to their daily ration of 15 grams, which was provided each morning. The weight of the rats and serological parameters (glycemia, cholesterol and triglycerides) were measured and compared according to the three diets administered. The conducted measurements showed that the weight of the rats increased significantly (20.95 g) under H diet in comparison to those with diet S. The SP diet allowed a return to normal weight change (19.25 g) after 67 days. Glycemia, total cholesterol, triglycerides and LDL- C (low-density lipoprotein cholesterol), which increased very significantly in diet H (0.53 g/L, 0.25 g/L, 0.2 g/L respectively), have decreased in SP diet to be on the same line as the values recorded in diet S (0.35 g/L, 0.62 g/L, 0.46 g/L respectively). However, HDL-C (high-density lipoprotein cholesterol) rate is less influenced by diet change. All the results obtained are in favor of a beneficial effect of Spirulina on metabolic sphere of Wistar rats, hence the interest of its incorporation in the human diet.